1988
DOI: 10.1111/j.1749-6632.1988.tb32960.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Patterns of Gait in the Healthy Old

Abstract: If the influences of aging processes on gait are to be understood, gerontologists must become better versed in experimental methodology appropriate to locomotion research. They must also begin to conduct experiments that move beyond mere description. Systematic research efforts that are interdisciplinary in nature and that incorporate several types of gait analyses will be needed to discover the causes of adaptations and impairments of gait in the aged. Certainly, this will not be easy to accomplish; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
61
1
7

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 30 publications
6
61
1
7
Order By: Relevance
“…A walking economy curve exists for each subject, with the self-selected preferred pace typically representing the walking speed yielding the lowest energy expenditure per meter traveled. 21 This is the most economical walking speed, and velocities above and below this point are accomplished at higher energy costs. The poorer walking economy of PAD subjects ultimately increases the physiological challenge of given ambulatory tasks performed throughout the course of the day.…”
Section: Discussionmentioning
confidence: 99%
“…A walking economy curve exists for each subject, with the self-selected preferred pace typically representing the walking speed yielding the lowest energy expenditure per meter traveled. 21 This is the most economical walking speed, and velocities above and below this point are accomplished at higher energy costs. The poorer walking economy of PAD subjects ultimately increases the physiological challenge of given ambulatory tasks performed throughout the course of the day.…”
Section: Discussionmentioning
confidence: 99%
“…First, in terms of kinematics, walking speed and metabolic demand are related to each other according to a U-shaped curve, whose central region is the region in which the metabolic cost of walking is minimized [3,5]. As our patients, according to the recommendations of the American Thoracic Society [15], performed the 6mWT over ground at their individually selected maximal speed, for each patient we were able to assess only one point of the speed-metabolic demand curve before and after the rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the preferred speed of walking tends to decline with advancing age and to walk a given distance older persons consume more metabolic energy than younger adults across all speeds [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers reported that older adults were less economical than younger adults while walking at various speeds (8,10,16). Conversely, economy of mobility appears to be unaffected by aging for individuals who maintain higher levels of physical activity (1,15,17).…”
mentioning
confidence: 99%